2019
DOI: 10.1002/solr.201900457
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Inorganic CsPb0.5Sn0.5I2Br Perovskite Compounds by Antioxidant Tea Polyphenol

Abstract: Implementation of inorganic perovskite compounds and reduction toxicity of lead are important for developing sustainable and renewable photovoltaic power generation. The inorganic Pb/Sn binary metal halide perovskites offer a perfect opportunity for tuning optical bandgap and thus hold significant potential in emerging technologies such as solar cells. However, an easy oxidation of Sn2+ to Sn4+ has become one of the main issues for achieving efficient and stable Sn‐based perovskite solar cells (PSCs). Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…The use of stabilizers such as antioxidizing agents to regulate the detrimental chemical reactions and inhibit the photooxidation of the photoactive materials may be a promising strategy to enhance the stability of NFA OSCs, considering the successful application of several stabilizers in biology, perovskite solar cells (PSCs), and polymer:fullerene OSCs. [ 178,225–228 ] For example, the inexpensive natural antioxidants uric acid, [ 229 ] tea polyphenol, [ 230 ] and ascorbic acid [ 231 ] have been used in tin‐based PSCs to prevent the oxidation Sn 2+ , thereby resulting in significantly improved device stability. It has been found that a set of structurally varied hindered phenols can stabilize the lifetime of P3HT:PCBM devices without compromising their performance, owing to the hydrogen donation and radical scavenging properties of hindered phenols which can significantly reduce the radicals within the photoactive layer.…”
Section: Toward Superior Stability Of Nfa‐based Oscsmentioning
confidence: 99%
“…The use of stabilizers such as antioxidizing agents to regulate the detrimental chemical reactions and inhibit the photooxidation of the photoactive materials may be a promising strategy to enhance the stability of NFA OSCs, considering the successful application of several stabilizers in biology, perovskite solar cells (PSCs), and polymer:fullerene OSCs. [ 178,225–228 ] For example, the inexpensive natural antioxidants uric acid, [ 229 ] tea polyphenol, [ 230 ] and ascorbic acid [ 231 ] have been used in tin‐based PSCs to prevent the oxidation Sn 2+ , thereby resulting in significantly improved device stability. It has been found that a set of structurally varied hindered phenols can stabilize the lifetime of P3HT:PCBM devices without compromising their performance, owing to the hydrogen donation and radical scavenging properties of hindered phenols which can significantly reduce the radicals within the photoactive layer.…”
Section: Toward Superior Stability Of Nfa‐based Oscsmentioning
confidence: 99%
“…[12][13][14][15] However, the inferior stability and low device performance of CsSnI 3 -based PSCs have been widely observed, which originate mainly from the chemical instability of Sn 2þ component and nonuniform perovskite crystalline layers. [16,17] As an essential inhibitor of Sn 4þ , SnF 2 has been reported to decrease the conductivity of tin-based perovskites and alleviate the oxidation of Sn 2þ . [18] SnF 2 also acts as a tin compensator to supply Sn 2þ .…”
Section: Introductionmentioning
confidence: 99%
“…The elements of Sn and Pb within the same main group have similar ns 2 np 2 electronic configuration [6][7][8][9]. Especially, the Snbased perovskites are promising for solar energy harvesting in view of ideal optical bandgaps (1.2-1.4 eV), high optical absorption coefficient as well as high carrier mobility (~585 cm 2 V À1 s À1 ) [10,11].…”
mentioning
confidence: 99%
“…One major drawback of Sn/Pb binary metal inorganic perovskites is their low chemical stability due to an easy Sn 2+ oxidation. To deal with this issue, antioxidant tea polyphenol was proposed to stabilize CsPb 0.5 Sn 0.5 I 2 Br (with an optical bandgap of 1.44 eV) as light absorber in solar cells using all-inorganic TiO 2 /Al 2 O 3 /NiO/carbon framework [9]. The optimized device exhibited an impressive PCE of 8.10% as well as decent operational stability (maintained 90.1% of its initial PCE under AM 1.5G one sun illumination with maximum power point tracking for 200 h in N 2 filled glove box).…”
mentioning
confidence: 99%
See 1 more Smart Citation